The good son : JFK Jr. and the mother he loved - Andersen, Christopher P. (Gallery Books, 2014)
Like many parents and children, Jacqueline Kennedy Onassis and JFK Jr. shared an intense, tender, and often tempestuous bond. It was, quite simply, the most important relationship in John's life. With riveting insight, Andersen reveals how mother and son influenced, challenged, and supported each other through good times and bad, unveiling startling new details about a family we thought we already knew: John's reaction to his mother's bout with suicidal depression and growing dependence on prescription drugs; the surreal and ultimately catastrophic impact of the Onassis years; the premonitions that terrified Jackie about John's fate; Jackie's success at keeping John away from his hellraising cousins, and his complicated relationship with the rest of the clan; the power she wielded over his affairs with Madonna, Sarah Jessica Parker, Daryl Hannah, and others; how John privately handled the scandalous revelations about his parents' marriage; the secrets about John's own turbulent marriage and his senseless death. Bittersweet, provocative, thoughtful and inspiring, this is the often heartbreaking tale of two lives tested by history and tragedy.--From publisher description.